Power Control of DFIG-generators for Wind Turbines Variable-speed - Ihedrane Yasmine; El Bekkali Chakib; Bossoufi Badre (International Journal of Power Electronics and Drive Systems (IJPEDS), 2017)
In this paper, we focus on the modeling and control of a wind power system based on a double-fed induction generator DFIG. We proposed a technique of active and reactive power control to improve the performance and dynamics of variable speed wind system. The objective of the modeling is to apply the direct and indirect vector control stator flux orientation to control independently, the active and reactive power generated doubly-fed induction generator (DFIG). The simulation results are tested and compared in order to evaluate the performance of the proposed system.